Writing in the doctorate: textual quality, argumentation and conceptions about writing - Valdés-León, Gabriel; González Riffo, Javier; Oyarzún Yáñez, Romina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study aims to investigate the relationship between the conceptions about writing those doctoral students have and their relationship with the textual and argumentative quality that texts written by them have. 31 texts produced by the doctoral students were reviewed and the textual quality and the argumentative quality were evaluated; then, a writing process questionnaire was applied, which allowed knowing the students’ conceptions about the two mentioned variables. It was found that the dimensions ‘blocking’ and ‘procrastination’ affect the quality of writing, while ‘transformation of knowledge’ is related to argumentative quality.